PEMBUATAN KAIN TENUN IKAT MAUMERE DI DESA WOLOLORA KECAMATAN LELA KABUPATEN SIKKA PROPINSI NUSA TENGGARA TIMUR - Elvida, Maria Nona (HOLISTIK, Journal Of Social and Culture, 2015)
The tied woven-cloth is part of variety culture as cultural Nusantara heritage have to be preserved because can enrich typical Indonesian with motives and pattern which the various variety .The difference to its geographic location consisting of some of the islands resulting in our range of a kind of cloth and variety of the decoration . In Sikka district still saved a lot of products that are already known by the public or by the outer provinces, one of which is a woven-cloth binding . Wololora already known as tied woven-cloth producing areas, ranging from silk to weaving. Natural silk industry in the Wololora village, cultivated with silk thread as a sarong . The tied woven-cloth craftsmanship Maumere people in the Wololora village only done by women and people former times they make cloth woven connective by the use of basic cotton .Whereas now they products using materials from the factory . the tied woven-cloth craftsmanship Maumere in Wololora village market has resulted in them, most the tied woven-cloth was used in order to marriage and others. Weaving has become a philosophy of life for women in the Wololora village. Indeed , the women weavers , not only weave a piece of cloth with a sale value economically , but they also compose and weave motifs of history, culture, values of life, village identity, moral and social, as well as their distinctiveness as women. Woven-cloth heritage, so that the current generation and the future do not forget the color of his own culture . Keywords: woven-cloth, craftsman, values